Question
Answers

If the derivative of \[\left( {ax - 5} \right){e^{3x}}\] at \[x = 0\] is \[ - 13\], then the value of \[a\]is equal to
\[
  (A){\text{ 8}} \\
  (B){\text{ - 5}} \\
  (C){\text{ 5}} \\
  (D){\text{ - 2}} \\
  (E){\text{ 2}} \\
 \]

Answer Verified Verified
Hint:- Use the product rule to find derivatives.

Let, y\[ = \left( {ax - 5} \right){e^{3x}}\] (1)
As given in the question that the value of derivative of y with respect to x at \[x = 0\]is \[ - 13\].
As, y is a function of x. So, we can get the derivative of y easily by using product rule.
Which states that if u and v are two functions then,
\[ \Rightarrow \left( {\dfrac{{d(uv)}}{{dx}}} \right) = u\dfrac{{dv}}{{dx}} + v\dfrac{{du}}{{dx}}\]
So, here u\[ = {e^{3x}}\] and v\[ = \left( {ax - 5} \right)\]
So, differentiating equation 1 with respect to x. We get,
\[ \Rightarrow \dfrac{{dy}}{{dx}} = {e^{3x}}\dfrac{{d(ax - 5)}}{{dx}} + (ax - 5)\dfrac{{d({e^{3x}})}}{{dx}}\] (By using product rule)
\[ \Rightarrow \dfrac{{dy}}{{dx}} = {e^{3x}}(a) + (ax - 5)3{e^{3x}}\]
Now, putting \[x = 0\] in the above equation. We get,
 \[ \Rightarrow {\left( {\dfrac{{dy}}{{dx}}} \right)_{x = 0}} = {e^0}(a) + (a(0) - 5)3{e^0}\]
As, given in the question, the derivative of the given function i.e. y at \[x = 0\] is \[ - 13\]. So,
\[ \Rightarrow - 13 = a - 15\]
\[ \Rightarrow a = 2\]
Hence, the correct option is E.

Note:- Whenever we come up with this type of problem where we are given with a function and the value of the derivative of that function at a given point, we first calculate the derivative of that function at a known point, then equate it with the given value of the derivative of the function at that point to get the required value of the variable.
Bookmark added to your notes.
View Notes
×